Production and extraction of phytotoxins from Colletotrichum dematium FGCC# 20 effective against Parthenium hysterophorus L. - Singh,Jaya (2010)
The aim of this work was to study the herbicidal potential of Cell free culture filtrate of Colletotrichum dematium FGCC#20 against Parthenium by employing different bioassays i.e. shoot-cut, seedling, detached leaf and seed germination. On solvent extraction of the Cell free culture filtrate, Ethyl acetate extracted fraction showed the presence of phytotoxic moiety.